Найдите корни уравнений: 1) (2y - 3) * (5y + 1) = 2y + 2/5 ; 2) -y * (y + 7) = (2 + y) * (y - 2)

limbo03rus limbo03rus    2   19.11.2019 12:11    0

Ответы
Lenchik632992 Lenchik632992  05.05.2020 18:07

Объяснение:

1) (2y - 3) * (5y + 1) = 2y + 2/5

10y²+2y-15y-3=2y+2/5

10y²-15y-3=2/5  // * 5

50y²-75y-15-2=0

50y²-75y-17=0

Δ=5625+3400=9025

√Δ=95

y1=(75-95)/100=-0,2

y2=(74+95)/100=1,7

2) -y * (y + 7) = (2 + y) * (y - 2)

-y²-7y = y^2-4

-2y²-7y+4=0  // *(-1)

2y²+7y-4=0

Δ=49+32=81

√Δ=9

y1=(-7-9)/4=-4

y2=(-7+9)/4=1/2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра